Choice and conscience: Lessons from South Africa for a global debate - Nabaneh, Satang (PULP Emerging Voices Series, 2023)
Choice and Conscience offers a fresh and insightful perspective on the highly debated issue of conscientious objection in abortion care. Satang Nabaneh's socio-legal approach, which draws on both traditional legal scholarship and African feminist intellectual traditions, provides a nuanced understanding of how legal norms construct and maintain power relations. By focusing on the experiences of nurses in South Africa, Nabaneh explores the complexities of conscience, discretionary power, and socio-cultural and political factors that influence nurses' decisions about whether or not to conscientiously object. In the wake of the recent rollback of abortion rights in the United States and the trend towards liberalisation within the African region, Nabaneh provides an important African perspective on how the international human rights framework should strike a contextual balance between freedom of conscience and ensuring access to abortion. Choice and Conscience will interest lawyers, activists, policymakers, scholars, and students exploring the dynamic intersections of law, healthcare, and gender politics.